IMPLEMENTASI PENDIDIKAN AL-ISLAM DAN KEMUHAMMADIYAHAN (AIK) DALAM PEMBINAAN KARAKTER MAHASISWA DI PERGURUAN TINGGI MUHAMMADIYAH - Fasich Firdaus; Ishomuddin Ishomuddin (As-Sulthan Journal of Education, 2026)
This study examines the implementation of the Al-Islam and Kemuhammadiyahan (AIK) curriculum in fostering student character at Institut Ahmad Dahlan Probolinggo. Character education is a central objective of Muhammadiyah and ‘Aisyiyah Higher Education Institutions (PTMA), where character formation has been embedded as a core educational mission since their establishment. Within the PTMA framework, character education is institutionally realized through Al-Islam and Kemuhammadiyahan (AIK) education. This study employed a qualitative descriptive approach. Data were collected through in-depth interviews, observations, and document analysis, and analyzed using data reduction, data display, and conclusion-drawing techniques. The findings indicate that Institut Ahmad Dahlan Probolinggo has systematically developed and implemented character education through the AIK curriculum, encompassing institutional policies, curriculum structure, and organizational governance. The implementation of the AIK curriculum has contributed positively to student character development. However, it has not yet fully achieved the expected outcomes. Several aspects require improvement, particularly in strengthening learning materials and instructional methods that remain predominantly cognitive, limiting the internalization of character values in affective and behavioral domains. Despite these limitations, the managerial implementation of the AIK curriculum has been well structured and consistently applied.